A novel SMS application with GSM control on numerator systems - (:unkn) unknown (My University, 2014)
0

Numerator systems are widely used in various fields, sorting, and structures to ensure regular functioning. They are used today in places such as banks and hospitals to minimize the time spent waiting in a queue, and various studies have been undertaken to achieve efficiency in the workplace. At the beginning of these studies, numerator systems, which have been integrated into the short message service (SMS) application, have been used efficiently. With this application, to supply the required information to the user in the fastest way, a numerator system is developed by utilizing radio frequency communications and the SMS message structure. The application system in this study includes hardware and software sections. The hardware section is designed using a keypad, microcontroller, and liquid crystal display as the user interface unit, and it also consists of a power supply feeding the system. The software section consists of the microcontrollers\' required software to control and operate the system, software for the elements used as the user interface unit, and the menu program software that the users will notice.
Keywords: Mühendislik, Elektrik ve Elektronik